Recharge Area on the Slopes of Volcano Based on Geological Setting, Content of Deuterium and Oxigen Isotopes of Groundwater Chemistry: Case Study on the Slopes of Salak Mountain, West Java - . Hendarmawan; . Satrio (JOURNAL OF TROPICAL SOILS, 2011)
Indonesian is huge areas that have the highest precipitation in the world, therefore water deficit of groundwater is   often happened at anywhere. This study was related to determination of recharge area with approached by combining geological setting, stable isotopes and chemictry content of groundwater. Case study was carried out at surrounding the Cicurug area, Sukabumi Prefecture, West Java Province.  The area is the slopes of Salak Mountain that have elevation of 400 until 1,200 m mean sea level (msl). While, much groundwater supplies industry activities on elevation 450-500 m msl. Based on data and result analysis of the studies, the recharge areas was not around peak of mountain or near, but water infiltrated on elevation of  700-800 m msl for groundwater exploited by industries. Therefore, the accurate determination of recharge area becomes a key for the groundwater sustainability.